Experimental Investigation of Terahertz Wave Scattering by Statistically Controlled Rough Surfaces - Alissa, Mai; Friederich, Benedikt; Kolpatzeck, Kevin; Czylwik, Andreas; Kaiser, Thomas (IMWS-AMP 2019 - 2019 IEEE MTT-S International Microwave Workshop Series on Advanced Materials and Processes for RF and THz Applications, 2019)
In this work, the experimental investigation of electromagnetic wave scattering by statistically controlled rough surfaces in the lower THz band is demonstrated. Rough surfaces with height fluctuations following normal statistics are fabricated using two different 3D printing techniques. The results presented here confirm that the surface roughness has a noticeable effect on the level of the diffuse scattering energy. In the future, the applied method can be used to validate analytical models as well as to gain scattering patterns from more complicated rough surface structures which fall outside the limits of most analytical approximations.
Created from Fastlane, Scopus look-up
Keywords: scattering measurements; statistically controlled rough surfaces; THz communication